2013
DOI: 10.1002/cncr.28130
|View full text |Cite
|
Sign up to set email alerts
|

Soluble human epidermal growth factor receptor 2 (HER2) levels in patients with HER2‐positive breast cancer receiving chemotherapy with or without trastuzumab: Results from North Central Cancer Treatment Group adjuvant trial N9831

Abstract: Purpose IncreasedsHER2 is an indicator of poor prognosisin HER2+ metastatic breast cancer. This study evaluated the levels of sHER2 during treatment and at time of recurrence in the adjuvant N9831 clinical trial. Patients and Methods Aims were to describe sHER2 levels during treatment and at time of recurrence in patients randomized to Arms A (standard chemotherapy), B (standard chemotherapy with sequential trastuzumab) and C (standard chemotherapy with concurrent trastuzumab). Baseline samples were availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Biomarkers could potentially be developed by extending work being conducted in patients with HER2+ breast cancer. For example, the cleaved extracellular domain of HER2, termed soluble HER2 (sHER2), can be detected in the blood of patients with metastatic HER2+ breast cancer and is a prognostic biomarker [54]. …”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers could potentially be developed by extending work being conducted in patients with HER2+ breast cancer. For example, the cleaved extracellular domain of HER2, termed soluble HER2 (sHER2), can be detected in the blood of patients with metastatic HER2+ breast cancer and is a prognostic biomarker [54]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, we also determined the approximate concentrations (Table S1, Supporting Information) of target protein biomarkers from each tested patient and healthy control samples based on the established calibration curves (Figure b). It was observed that the determined target concentrations for each of the relevant biomarkers (HER2‐breast cancer[16a] and MUC16‐ovarian cancer) from patients samples were within the clinically relevant range. [16a] However, the resulting variation in the detected target levels of HER2(+) and MUC16(+) patients could be attributed to the cancer stage and also inherent protein expression of HER2[16b] or MUC16 that could vary across individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, simultaneous capture and multiplexed detection was performed on human epidermal growth factor receptor 2 (HER2); Mucin 1, cell surface associated (MUC1); epidermal growth factor receptor (EGFR); and Mucin 16, cell surface associated (MUC16), which are overexpressed in breast, lung, and ovarian cancer, respectively . Notably, HER2 is widely considered as an important biomarker for breast cancer therapy and believed to have close correlation with hormonal therapy and drug treatment . Similarly, MUC16 is potentially the only recommended tumor biomarker for the clinical diagnosis and management of ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
“…In the N9831 adjuvant breast cancer trials, early stage HER2-positivity was identified as a biomarker of clinical outcome and disease progression (54). Moreno-Aspitia et al (55) evaluated sHER2 levels at the time of relapse using a sample from the N9831 clinical trial and found that DFS was lower in patients with sHER2 levels >15 ng/ml, compared with patients with lower levels of sHER2 (HR=2.36; 95% CI=1.19-4.70; P=0.01). Therefore, in early stage HER2-positive breast cancer, sHER2 was found to be a suitable prognostic biomarker for relapse, and survival in relapsed patients.…”
Section: Soluble Human Epidermal Growth Factor Receptor 2 (Sher2)mentioning
confidence: 99%